Classic Christmas favorites : 10 Holiday Favorites - Griffith, Andy; 1926-2012.; 1932-; 1936-1992.; Winters, Shelley; Grey, Joel; Miller, Roger; 1887-1969; Gorshin, Frank; Karloff, Boris; Carney, Art; 1918-2003; et al. (Burbank, California, 2008)
"All in one evergreen collection: 10 animated specials youve grown up with and loved - including 3 new to DVD!"- -Container.
Disc 1 --
Keywords: Christmas; Christmas; Juvenile films; Juvenile works; Christmas television programs; Christmas films; Childrens films; Animated television programs; Animated films